The Tobelo Dalam People on Halmahera Island, Indonesia “Indigenous people or Vulnerable Group” - M Nasir Tamalene; Nam Rumkel; Adi F Mahmud (UNIVERSITAS PAKUAN, 2025)
AbstractThis study aims to examine the legal and social status of the